Жанр ранг-баранглиги театрнинг жамият ҳаётига маънавий – маърифий таъсирини ошириш омили сифатида - Алланбаев, Р (SCIENCE and SOCIETY, 2021)
The study of theatrical repertoire allowed us to determine the specificity of the object of our research in this trend. The characters on the stage include fam- ily members with conflicting worldviews, business people, successful people, those who have fallen into the whirlpool of religious extremists, people who have survived the hardships of life and those who achieved success.
Keywords: theater; music; material and technical; audience; art history; dramatic works